THE EFFECT OF IRAES READING TECHNIQUE ON ENHANCING CRITICAL THINKING IN ENGLISH READING AMONG HIGH SCHOOL STUDENTS IN SICHUAN, CHINA - Wen Jia; Nor Hazwani Munirah Lateh (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
English language has become a major concern among China government, as their economy growing need a diverse language in communicating with the foreigner, including expand their economy outside Chine. However, English language adoption among the student remain low, by that situation has make a hurdle for the government to escalated China economy into next step. Therefore, the IRAES approach has become part of the point in embedment of English education teaching and learning among high school in Sichuan, China. The analyse have been conducted among 200 respondents for each Group A and B each with pre-test and post-test analysis. The result has showed that the Group A with IRAES intervention, has significantly improved the student in term of their critical thinking skills and reading comprehension. This result contributed and benefited to the relevance stakeholders, particularly for government, students and teacher in teaching and learning approaches policy improvement.